Research on the Design Process and Approaches for Low-Carbon Ecological Parks in Urban Areas of Northwestern China - Jingmao WANG; Haobo XU; Tao ZHANG; Jie GAO (Fengjing Yuanlin, 2025)
ObjectiveThe global community has increasingly aligned with the carbon peaking and carbon neutrality goals — as a cornerstone of climate action. Within urban ecosystems, park green spaces emerge as a pivotal contributor to carbon sink capacity, accounting for over 60% of the total urban carbon sequestration capacity in semi-arid regions according to recent research. In Northwest China, where ecological vulnerability (e.g., annual precipitation below 300 mm) intersects with rapid urbanization, developing a region-specific planning and design framework for low-carbon ecological parks and their phytoscapes is not merely advantageous but imperative. This framework must address three core challenges: 1) Optimizing plant species selection for drought resistance and high carbon sequestration rates (e.g., Populus simonii, Hippophae rhamnoides); 2) integrating water-efficient irrigation systems with renewable energy infrastructure; and 3) balancing recreational functionality with ecological restoration priorities. By leveraging geospatial analysis and lifecycle carbon accounting, such a methodology can transform green spaces from passive carbon reservoirs into active climate mitigation tools, directly supporting the 2060 carbon neutrality target.MethodsThis research takes the low-carbon design of plantscape in Tongchuan Peony Garden as an entry point, applies relevant modes and solutions combining theoretical research, case summarization and research and measurement to the aforesaid project in order to test the operability and applicability of relevant low-carbon design indexes, and systematically and scientifically puts forward a guiding framework for the low-carbon design process of the Peony Garden. In addition, taking plantscape design as a basis, the research puts forward strategies and ideas for the practice of plantscape design of park green spaces from a low-carbon perspective, and provides reference for the low-carbon plantscape design of urban park green spaces afterwards. Through field research of five parks in Tongchuan New District with similar environmental conditions, the research analyzes the status and influencing factors of park plantscape carbon sinks, and screens 38 typical samples according to the differences in the plantscape characteristics and functional orientation of the research site for characterization. Furthermore, the research calculates the carbon sequestration capacity of individual plants and sample communities based on relevant software, analyzes the overall layout of the parks, and figures out the carbon neutrality years of such parks.ResultsBased on the significance of low-carbon design of existing parks and the background of related problems, this research puts forward the urban low-carbon design process of “target positioning of ecological and functional synergy – spatial layout and functional zoning of carbon sinks – layout of low-carbon design index elements – low-carbon building and construction – low maintenance and management and carbon neutrality years” for the Northwest China region through theoretical research and summarization of practical experience. The aforesaid park design process emphasizes that plantscape is the key to enhancing carbon sinks, and according to the differences in local plantscape characteristics and functional orientation in combination with ecological services and spatial synergy, a total of 9 plantscape types are obtained and divided into four categories: Park roads and squares, park woodlands and grasslands, park rivers and lakes, and special park habitats. A total of 24 plantscape carbon sink enhancement models applicable to different site conditions are proposed. The overall park layout is analyzed and carbon neutrality years calculated, and the design of plantscape carbon sink enhancement is proposed to be carried out from the whole process of plantscape zoning layout, community configuration, type and species selection, planting construction, and maintenance and management. The low-carbon design practice of Tongchuan Peony Park is implemented, and the average carbon sink capacity of different zones of the project is quantitatively compared from the perspective of function and landscape characteristics.ConclusionThrough the synergistic consideration of ecological functions and practical uses, a design process and optimization method based on the integration of ecology and functionality are proposed, providing scientific guidance for the practice of low-carbon ecological parks. In summary, this research take the Tongchuan Peony Park planning and design project as an example to explore the plantscape design of urban parks under the perspective of low carbon, with the aim of providing scientific guidance for relevant research practices in this field.